Outcome of Surfactant Replacement Therapy in Premature Neonates in ICU of Ibn Sina Teaching Hospital of Sirte, Libya in Period Between May – 2019 to May – 2022 - Intisar Abushamala; Hameda Elzarouk Eltaib (Sirte Journal of Medical Sciences, 2023)
Introduction :Respiratory distress syndrome (RDS) is an acute lung disease of preterm babies caused by surfactant insufficiency . Decreased surfactant results in insufficient surface tension in the alveolus during expiration leading to alveolar collapse , atelectasis , impaired gas exchange , severe hypoxia and acidosis , leading to respiratory failure . Surfactant replacement therapy (SRT) is now accepted as the standard treatment of preterm babies with RDS . Objective : The objective of this study was to analyze the incidence and outcome of surfactant replacement therapy in preterm babies with RDS . Methodology : This is Quantitative retrospective study , conducted in Neonatal Intensive Care Units (NICU) of Ibn Sina Teaching Hospital , Sirte , Libya . Study duration was of three years period ( May – 2019 to May – 2022 ) . Preterm babies from 24 wks to 36 wks of gestation with RDS received SRT were included in this study . The surfactant was administrated intra- tracheally according to standard procedures . Results :In this study of 41 preterm babies with RDS received SRT , 30 ( 73.2% ) were male and 11 ( 26.8% ) were female . The mean gestational age was 33.12 weeks . Among 41 preterm babies with RDS receiving SRT , 21 ( 51.2% ) discharged from the hospital and 20 ( 48.8% ) expired . Maximum survival was seen in the gestational age of ≥32 wks and birth weight ≥ 1500 gms . Conclusion : The use of SRT has improved the survival outcome and decreased the associated morbidities in babies with RDS . The maximum impact of survival was seen in the oreterm babies of ≥ 32 weeks with birth weight of ≥ 1500 grams .